Gestión de talento Humano en el Comercial Dismero de la ciudad de Babahoyo - LOZADA JAEN, JOVI JAVIER (2018)
Since the emergence of organizations as units for the exchange of goods and services, we have found the concern to create an organization system, which provides the differentiation of the projects of a company, in relation to the competition, marking a management style to obtain benefits and utilities for their owners